2017
DOI: 10.1590/0034-7329201700202
|View full text |Cite
|
Sign up to set email alerts
|

The South American Defense Council: the Building of a Community of Practice for Regional Defense

Abstract: • Este é um artigo publicado em acesso aberto e distribuído sob os termos da AbstractWhile the South American Defense Council has been analyzed as a security community, we argue that it is best described as an early stage community of practice, since it has successfully set in motion a regular interaction dynamic between numerous defense actors, as we demonstrate with concrete examples. We further discuss political support as a prerequisite for regional defense identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Examining views of the CDS's imperfections and limitations, I have shown that the original intention was to create a forum dedicated to producing alternative strategic thinking about hemispheric understandings of regional security. In this way, and regardless of the extent to which it succeeded, thinking, debating, teaching and learning were featured as relevant cooperation practices inside the CDS (Vitelli 2017). In order to address the task of crafting a security concept of its own, the CDS created the CEED as a permanent unit for research and strategic thought, and, in 2014, established an educational institution in respect of defence issues -ESUDE -aimed at coordinating existing and future educational cooperation on security.…”
Section: Security Concepts and Military Roles In Latin Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Examining views of the CDS's imperfections and limitations, I have shown that the original intention was to create a forum dedicated to producing alternative strategic thinking about hemispheric understandings of regional security. In this way, and regardless of the extent to which it succeeded, thinking, debating, teaching and learning were featured as relevant cooperation practices inside the CDS (Vitelli 2017). In order to address the task of crafting a security concept of its own, the CDS created the CEED as a permanent unit for research and strategic thought, and, in 2014, established an educational institution in respect of defence issues -ESUDE -aimed at coordinating existing and future educational cooperation on security.…”
Section: Security Concepts and Military Roles In Latin Americamentioning
confidence: 99%
“…All of them can be accessed by sending an email to basededadoscds@gmail.com. For a detailed analysis of CDS activities, seeVitelli (2016Vitelli ( , 2017.11 Saint-Pierre (2011) noticed the deliberate exclusion of multidimensional security issues in the CDS's early stages.12 The 2016 edition of the RESDAL Atlas does not list Brazil as a country that employs its military for controlling prison perimeters. However, I decided to include Brazil in view of a government decision in January 2017 to use the army for inspections of state prisons.…”
mentioning
confidence: 99%
“…In this sense, important conceptual aspects must be considered. The first is that the member states defined the organization in terms of “defense.” The second is composed of the terms “consultation,” “cooperation,” and “coordination.” It suggests that, although the Venezuelan thesis on the construction of a mechanism oriented openly to “collective defense,” meaning a military alliance, did not triumph (Comini, ; Frenkel & Comini, ; Sánchez Cabarcas, ; Vitelli, ), important conceptual elements of collective defense and security remained in the founding statute.…”
Section: The Cds Performance: a Descriptive Inferencementioning
confidence: 99%
“…For this research, an exercise in descriptive inference was undertaken, without arriving at the stage of applying process‐tracing tests. The reason is that, until now, the research agenda on the CDS has made little progress in the study of its performance (Vitelli, ; Vaz et al, ), making it premature to try to establish causality based on the validation of multiple hypotheses (Bennett, ; Collier, ; Van Evera, ). It is impossible to ignore the fact that there are still debates about what process tracing is and what it is not, especially with regard to the establishment of causal mechanisms (Beach & Pedersen, , pp.…”
Section: The Cds Performance: a Descriptive Inferencementioning
confidence: 99%
See 1 more Smart Citation